Optimization of Power Management Strategy for Parallel Air-Fuel Hybrid System. (May 2017) - Yang, Shu-Yu; Sung, Cheng-Kuo; Huang, Chih-Yung
Abstract: Air Engines (AE) are commonly designed to work in combination with internal combustion engines (ICE) due to low energy density. The emission of heat from ICE boosts the efficiency of Air Engines, whereas the high-pressure gas from AE serves as a form of turbo charging for ICE, increasing its efficiency. Unlike batteries, the air tank that AE requires is not limited by certain restrictions in order to prolong its lifetime, therefore, the Air Hybrid System is believed to have great potential. There has already been quite some research on power management strategy of electric hybrid systems, however, little is done on Air hybrid systems. A numerical models of Air Hybrid Systems is established using MATLAB in this study, the characteristics of the model, such as the efficiency map and driving cycles are further analyzed to obtain the optimal energy management strategy for Air Hybrid Systems. These findings are expected to help the realization of physical models and the establishment of controller design. Through genetic algorithms, the optimal system structures, operation modes and power management strategies are found to ensure that both engines are operating within the most efficient range. Simulation results suggest that the efficiency of the Air Hybrid System is 26.13% higher comparing to a lone Air Engine.